Phrenic motor neuron adenosine 2A receptors elicit phrenic motor facilitation. (11th March 2018) - Seven, Yasin B.; Perim, Raphael R.; Hobson, Orinda R.; Simon, Alec K.; Tadjalli, Arash; Mitchell, Gordon S.
Abstract : Key points: Although adenosine 2A (A2A ) receptor activation triggers specific cell signalling cascades, the ensuing physiological outcomes depend on the specific cell type expressing these receptors. Cervical spinal adenosine 2A (A2A ) receptor activation elicits a prolonged facilitation in phrenic nerve activity, which was nearly abolished following intrapleural A2A receptor siRNA injections. A2A receptor siRNA injections selectively knocked down A2A receptors in cholera toxin B‐subunit‐identified phrenic motor neurons, sparing cervical non‐phrenic motor neurons. Collectively, our results support the hypothesis that phrenic motor neurons express the A2A receptors relevant to A2A receptor‐induced phrenic motor facilitation. Upregulation of A2A receptor expression in the phrenic motor neurons per se may potentially be a useful approach to increase phrenic motor neuron excitability in conditions such as spinal cord injury. Abstract: Cervical spinal adenosine 2A (A2A ) receptor activation elicits a prolonged increase in phrenic nerve activity, an effect known as phrenic motor facilitation (pMF). The specific cervical spinal cells expressing the relevant A2A receptors for pMF are unknown. This is an important question since the physiological outcome of A2A receptor activation is highly cell type specific. Thus, we tested the hypothesis that the relevant A2A receptors for pMF are expressed in phrenic motor neurons per se versus non‐phrenic neurons of the cervical spinal cord. A2A receptor immunostaining significantly colocalized with NeuN‐positive neurons (89 ± 2%). Intrapleural siRNA injections were used to selectively knock down A2A receptors in cholera toxin B‐subunit‐labelled phrenic motor neurons. A2A receptor knock‐down was verified by a ∼45% decrease in A2A receptor immunoreactivity within phrenic motor neurons versus non‐targeting siRNAs (siNT; P < 0.05). There was no evidence for knock‐down in cervical non‐phrenic motor neurons. In rats that were anaesthetized, subjected to neuromuscular blockade and ventilated, pMF induced by cervical (C3–4) intrathecal injections of the A2A receptor agonist CGS21680 was greatly attenuated in siA2A (21%) versus siNT treated rats (147%; P < 0.01). There were no significant effects of siA2A on phrenic burst frequency. Collectively, our results support the hypothesis that phrenic motor neurons express the A2A receptors relevant to A2A receptor‐induced pMF. Key points: Although adenosine 2A (A2A ) receptor activation triggers specific cell signalling cascades, the ensuing physiological outcomes depend on the specific cell type expressing these receptors. Cervical spinal adenosine 2A (A2A ) receptor activation elicits a prolonged facilitation in phrenic nerve activity, which was nearly abolished following intrapleural A2A receptor siRNA injections. A2A receptor siRNA injections selectively knocked down A2A receptors in cholera toxin B‐subunit‐identified phrenic motor neurons, sparing cervical non‐phrenic motor neurons. Collectively, our results support the hypothesis that phrenic motor neurons express the A2A receptors relevant to A2A receptor‐induced phrenic motor facilitation. Upregulation of A2A receptor expression in the phrenic motor neurons per se may potentially be a useful approach to increase phrenic motor neuron excitability in conditions such as spinal cord injury.